Analysis of CYP1B1 Gene Mutations in Patients with Primary Congenital Glaucoma - Chouiter, Leila; Nadifi, Sellama (Journal of Pediatric Genetics, 2017)
Primary congenital glaucoma (PCG) is the most common type of infantile glaucoma, yet it remains a relatively rare disease, because the disease is often transmitted in an autosomal recessive pattern. However, PCG occurs up to 10 times more frequently in certain ethnic and geographical groups where consanguineous relationships are common. The aim of this study was to investigate the distribution of mutations in the cytochrome P450 1B1 gene (CYP1B1) in patients with PCG among different populations around the world from 2011 until May 2016. We referred to the electronic databases, such as Medline, Clinicalkey, Scopus, and ScienceDirect, to search for articles that were published in this area. Nineteen records were included in this qualitative synthesis. CYP1B1 mutations were assessed in 1,220 patients with PCG and identified in 41.6% of them. According to these studies, 99 mutations including 60 novel mutations were found. Nonsignificant difference in the sex ratio has been reported. This current review shows that consanguinity plays an important role in the PCG pathogenesis and transmission; however, sporadic mutations have been found in some cases. A difference in penetrance was highlighted by some mutations. The CYP1B1 mutations were mostly found in the Middle East and the Maghreb with a rate of 64.8 and 54.4%, respectively, followed by Europe (34.7%), Asia (21.3%), and finally the United States (14.9%). Founder mutations in different geographical areas have been discovered. For instance, the p.Gly61Glu, p.Arg390His, p.Gly61Glu, c.4,339delG, p.E387Lys, and p.Val320Leu were considered founder mutations for Iran/Saudi Arabia, Pakistan, Lebanon, Morocco, Europe, and Vietnam/South Korea, respectively. Many common mutations in different countries were found, such as in Morocco, where its mutations were similar to seven other countries. These findings suggest that the ethnic differences and the geographical distribution of PCG give us a large CYP1B1 mutation pattern. Genetic tests looking for founder and common mutations should be the first step in genetic screening for patients with PCG.
Keywords: primary congenital glaucoma; CYP1B1; cytochrome P450; GLC3A